Anticipated Difficult Intubation Due to Polypoidal Squamous Cell Carcinoma on Posterior One Third of Tongue - Alka Chhabra; Sunanda Gupta; Preeti Saini; Kunal Chauhan (Research and Practice in Anesthesiology, 2018)
The most common type of tongue malignancy is squamous cell carcinoma (SCC) which constitutes about 36.5% of all oral malignancies. It usually presents as painless swelling which is often ignored by the patient until late when it is symptomatic because of demonstrable growth in the oral cavity.